Tree and tree-like species of Mexico: Asteraceae, Leguminosae, and Rubiaceae - Martin Ricker; Héctor Manuel Hernández Macías; Mario Sousa Sánchez; Helga Ochoterena (Revista Mexicana de Biodiversidad)
Trees or tree-like plants are defined here broadly as perennial, self-supporting plants with a total height ofat least 5 m (without ascending leaves or inflorescences), and with one or several erect stems with a diameter of atleast 10 cm. We continue our compilation of an updated list of all native Mexican tree species with the dicotyledonousfamilies Asteraceae (36 species, 39% endemic), Leguminosae with its 3 subfamilies (449 species, 41% endemic), andRubiaceae (134 species, 24% endemic). The tallest tree species reach 20 m in the Asteraceae, 70 m in the Leguminosae,and also 70 m in the Rubiaceae. The species-richest genus is Lonchocarpus with 67 tree species in Mexico. Threelegume genera are endemic to Mexico (Conzattia, Hesperothamnus, and Heteroflorum). The appendix lists all species, including their original publication, references of taxonomic revisions, existence of subspecies or varieties, maximum height in Mexico, and endemism status.